2021
DOI: 10.1002/jmv.27475
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effects of interferon β−1a on hospitalized patients with COVID‐19: SBMU Taskforce on the COVIFERON study

Abstract: Interferons are an essential part of the innate immune system and have antiviral and immunomodulatory functions. We studied the effects of interferon β‐1a on the outcomes of severe cases of coronavirus disease 2019 (COVID‐19). This retrospective study was conducted on hospitalized COVID‐19 patients in Loghman‐Hakim hospital from February 20, 2020 to April 20, 2020, Tehran, Iran. Patients were selected from two groups, the first group received interferon β‐1a in addition to the standard treatment regimen, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Interferons (IFNs) are fundamental agents of the innate immune system, thanks to their action against viruses and their immunomodulatory functions [ 58 ]. IFN-β, used as a treatment for hospitalized patients who are COVID-19 positive, has been demonstrated to have significant efficacy, as it may diminish the hospitalization time, the ICU admission rate, the need for invasive respiratory support and the mortality rate of patients with severe COVID-19 [ 58 , 59 ]. Despite this, there are a few individual cases that report the onset of AP due to IFN, and for that reason, it is included in Class III of the Badalov classification of drugs [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interferons (IFNs) are fundamental agents of the innate immune system, thanks to their action against viruses and their immunomodulatory functions [ 58 ]. IFN-β, used as a treatment for hospitalized patients who are COVID-19 positive, has been demonstrated to have significant efficacy, as it may diminish the hospitalization time, the ICU admission rate, the need for invasive respiratory support and the mortality rate of patients with severe COVID-19 [ 58 , 59 ]. Despite this, there are a few individual cases that report the onset of AP due to IFN, and for that reason, it is included in Class III of the Badalov classification of drugs [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interferon beta1-a (IFN-β1a) demonstrated considerable efficacy in COVID-19 patients in a recent clinical trial. Previous in vitro studies demonstrated interferon-β antiviral efficacy against the SARS virus (Fallahzadeh et al 2022 ). Both types of IFNs may cause diabetes mellitus because it has been documented that long-term therapeutic use of type I IFNs causes autoimmunity as well as the emergence of type 1 diabetes after treatment with type I IFNs (Pelegrin et al 1998 ).…”
Section: Association Between Covid-19 Treatment Drugs and Diabetesmentioning
confidence: 99%